Analisis Makna Simbolik Tradisi Pakkio’ Bunting Pada Perkawinan Adat Suku Makassar - Nosakros Arya Arya; Teguh Ardiansyah Sabir; Dhia Naufalia Ilmi; Akhyar (Connected: Jurnal Ilmu Komunikasi, 2022)
Marriage is an essential thing for a person—likewise, the views of the Bugis people. According to the opinion of the Bugis people, marriage is not the union of the two brides and groom in a husband-wife relationship. Still, marriage is a ceremony that aims to unite two prominent families that have previously become closer or deeper. The depth of the meaning of marriage for Bugis makes a series of ceremonies to respect the perka. In the customary marriage of the Bugis Makassar, there is a tradition that the community has carried out. One of those traditions is "Pakkio' Bunting." Pakkio 'Buntter' consists of two words, namely pakkio, 'which means the caller or welcome, and the pregnant bride or groom. Pakkio' Bunting poetry is tribal oral literature in a series of poetic lines used in the welcoming procession. When the groom and his entourage arrive at the bride's house, a man will say the Pakkio' pregnant poem. The research aims to practice the pakkio' pregnant tradition in Bugis Makassar traditional marriages today, which causes the Pakkio' Bunting tradition in Bugis customary marriages. Then identify the most reasonable efforts to maintain the Pakkio' Bunt tradition in the Makassar Bugis marriage tradition. The location of this research is Biringbulu District, Kab. Gowa, South Sulawesi Province. This research will use a qualitative descriptive approach. Based on the research results, the meaning of the pregnant pakkiok is related to the atmosphere of the newlyweds navigating the household ark, such as being responsible, respecting each other, accepting each other, and understanding each other.